Reading: A Motivating and Interactive Process - Santoyo Brigitte; Morales G. Lilia E. (Universidad Nacional de Colombia, 2000)
This research was primarily intended for those who are
professionally concerned with the teaching of a foreign language, and especially for those who consider reading to
be one of the most important sources for developing comprehension and production processes. We wanted our students to develop reading strategies by means of meaningful and motivating stories. Meaningful, because interesting stories encourage them to improve, and motivating, because they open the doors to multiple
possibilities, thereby reinforcing other abilities.